Perubahan Kebijakan Amerika Serikat Terhadap Irak Pada Executive Order 13780 - Muslima Diputri, Kireina Lucretia; Fasisaka, Idin; Widya Nugraha, A. A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
A BS TR A C T   T h i s research a ims t o d escribe t he U n i t ed State of A m erica's national interest t o c hange t heir f oreign policy regarding t he U nited S t a t e of America's d e c ision t o remove I r a q f rom t h e t r a v e l ban. T h is research uses a descriptive qualitative m ethod, a nd literature s o urces t o c o l l ect t he data. T h e   data   b e   analyzed   uses   t w o   m a in   c o ncepts,   w hich   are   national   i nterest   and   f oreign   poli c y c oncepts. T he results of t h is research a r e t he U nited S t ate o f A m e r i c a has a d efense interest w i t h I r a q.   F urthermore,   t he response f rom t he D epartment   of   D efense f or domestic   f actors,   and t he c ooperative attitude by I raq t o a nswer t he f ormer e x ecutive o r d er a s a n external f actor as a f f e c t i ng t he U nited S t a t e o f A m e r i c a's f oreign p o licy c hanged.   I r a q r e m oved f rom t he t ravel ban also ha s f ulfilled t he f irst national v i t a l interest of t he U nited S t a t e s o f America, a nd expected c ould m a i ntain t he national s ecurity o f t h e U nited State o f America f rom t e r r o r i sm .   Key Words         : United State of America, Iraq, Executive Order, National Interest, Foreign Policy changed